Pemanfaatan Plasma Nutfah Padi Varietas Lokal dalam Perakitan Varietas Unggul - Trias Sitaresmi; Rina H. Wening,; Ami T. Rakhmi; Nani Yunani; Untung Susanto (Puslitbang Tanaman Pangan, 2013)
Indonesia is rich in rice germplasm which functioning as genetic resources, consisting of local varieties and wild species. Million years ago, Indonesian archipelago was an integral part of the Asia continent, which is considered as the center of origin of rice. Vavilov postulated that India is the Center of Origin of rice and Indonesia could be considered as the Secondary Center of Origin of rice. Local varieties had been planted by farmers for many generations on specific agroecology, so that presumably they are resistant/tolerant to biotic or abiotic stresses on a specific location. Farmers had selected seeds from the population, based on good adaptation or god quality for the next planting season. They selected plants that have good grain quality and good cooking taste. Therefore, most of the local varieties have a good grain quality and their taste quality met the consumer’s preference. Germplasm research on rice in Indonesia had identified local varieties which are resistant/tolerant to pests and diseases including: ganjur, bacterial leaf blight, orange leaf blight, brown planthopper, leaf blast, neck blast, white striped leaf, tungro, drought, Al toxicity, Fe toxicity, tolerant to abiotic stress such as salinity, cold temperature, and shade. The local varieties had been used in the breeding program, however, the number of germplasm used as parental crosses is still low. Research on gene analyses, gene mapping, and study on the gene inheritance are needed, to facilitate an efficient use of the genetic resources. Use of local varieties as parental hybridization is recommended, to get superior specific genotype on the new varieties, so that released varieties should have a broad genetic variability.